2012
DOI: 10.5507/bp.2012.039
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of ESBL- and AmpC-positive Enterobacteriaceae in the gastrointestinal tract of community subjects and hospitalized patients in the Czech Republic

Abstract: Aim. The study aimed at analyzing ESBL-and AmpC-positive Enterobacteriaceae in the gastrointestinal tracts of university hospital inpatients and persons from the Olomouc Region community, and comparing the results with data from 2007. Methods. Bacteria were isolated from rectal swabs inoculated onto the ChromID TM ESBL selective medium (bioMérieux). Production of ESBL-type beta-lactamases was confirmed by the modified double-disk synergy test and AmpC enzyme production was detected by the AmpC disk test. ESBL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
1
24
0
3
Order By: Relevance
“…These results are similar to those obtained from patients in other works; Naseer et al reported a prevalence of 3.7% of AmpC among outpatients in Norway [18], and Li et al reported a prevalence of 1.9% [19]. These findings are nearly similar to those reported in the Czech Republic and Denmark (rates were1.1% and 2.4%, respectively) [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those obtained from patients in other works; Naseer et al reported a prevalence of 3.7% of AmpC among outpatients in Norway [18], and Li et al reported a prevalence of 1.9% [19]. These findings are nearly similar to those reported in the Czech Republic and Denmark (rates were1.1% and 2.4%, respectively) [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…Los resultados encontrados difieren a los trabajos realizados por otros autores: Husickova et al en República Checa, reportaron el 3,2% de portadores fecales de enterobacterias productoras de BLEE en sujetos de la comunidad (15) . Adriatahina et al en una unidad pediátrica de Madagascar, realizaron hisopados rectales el primer y el último día de hospitalización, se encontró un 21,2% de productoras de BLEE en las del primer día y al momento del alta se encontró el 57,1% (16) .…”
Section: Discussionunclassified
“…Es importante mencionar que en los últimos años se ha descrito el incremento de enterobacterias productoras de BLEE de la familia CTX-M (19) , en este estudio se encontró que la gran mayoría de los aislados productores de BLEE presentaban en gen bla CTX-M, el grupo de gen dominante en los estudios de portadores fecales de República Checa (15) , España (20) , India (2) , Madagascar (16) , Nigeria (17) , Francia (24) , Guinea-Bissau (25) y Japón (26) poniendo de relieve la importancia de este gen en la difusión global de BLEE. La BLEE tipo CTX-M tiene principalmente actividad sobre la cefotaxima y no sobre la ceftazidima; aunque en los últimos años la emergencia de variantes de CTX-M (CTX-M-15, CTX-M-16, CTX-M-27 y CTX-M-19) están mejorando su actividad frente a ceftazidima.…”
Section: Discussionunclassified
“…Considering the probable increase in infections with ESBL-producing bacteria in patients who are already carriers of these bacteria, recent studies on the rates of carriage in the community and the relation between carriage and infections are attracting attention. While rates of 1%-8% carriage in healthy populations were reported in various European countries between 2003 and 2007, the rates were found to be increasing over time (2)(3)(4). On the other hand, up to 50%-60% rates of carriage were reported from countries in Asia and Africa such as Egypt (5) and China (6).…”
Section: Introductionmentioning
confidence: 99%